The complete chloroplast genome sequence of the Trichosanthes Kirilowii Maxim. (Cucurbitaceae). Issue 1 (2nd January 2019) - Yang, Youxin; Li, Jingwen; Zhou, Qinghong; Shan, Nan; Zhu, Qianglong
Abstract: Trichosanthes kirilowii Maxim. is an essential traditional Chinese medicine used for various diseases. The complete chloroplast genome sequence of T. kirilowii has been determined in this study. The total genome size is 157, 481 bp in length and contains a pair of inverted repeats (IRs) of 26, 268 bp, which were separated by large single copy (LSC) and small single copy (SSC) of 86, 478 bp and 18, 467 bp, respectively. A total of 130 genes were predicted including 85 protein-coding genes, eight rRNA genes and 37 tRNA genes. Further, phylogenetic analysis confirmed that T. kirilowii belongs to the family Cucurbitaceae. The complete chloroplast genome of T. kirilowii would play a significant role in the development of molecular markers in plant phylogenetic and population genetic studies.